An exploration of brand love in the South African boutique music festival scene - Schoeman, Craig (The IIE, 2022)
This study aims to close the gap in research found in the local boutique music festival scene. It sets out to uncover the most important elements for building brand love in this experiential space. A qualitative approach was utilised to gain an understanding of what brand love looked like, from both the consumers’ and producers’ perspective. To achieve this, ten participants were individually invited to partake in a face-to-face interview. These participants included five festival organisers and five festival attendees. The study concluded that there was a strong correlation between the success of boutique music festival brands and their ability to incorporate mystery, sensuality and intimacy. Alongside this the study was able to uncover two types of people that attend these events. Some attendees were enticed by the social aspect, while the others were more attracted to the genre of music and the artists being showcased. Lastly the power of social media prevailed, as an important factor, for the success of these events.
Keywords: Music festivals; Consumer behavior; Outdoor events; Social media